2012
DOI: 10.1002/j.0022-0337.2012.76.11.tb05405.x
|View full text |Cite
|
Sign up to set email alerts
|

Cone Beam Computed Tomography in Dental Education: A Survey of U.S., U.K., and Australian Dental Schools

Abstract: Cone beam computed tomography (CBCT) is an excellent three-dimensional (3D) imaging modality. Traditional dental education has focused on teaching conventional (2D) imaging. The aims of this survey-based study were therefore to evaluate the incorporation of CBCT teaching in both the predoctoral/undergraduate (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 21 publications
0
44
1
2
Order By: Relevance
“…A few studies evaluated CBCT learning in Dental Schools predoctoral courses 1,7,9,10 . None of these studies, however, evaluated and compared the students test scores and performance over the semester while providing both online and in-class learning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few studies evaluated CBCT learning in Dental Schools predoctoral courses 1,7,9,10 . None of these studies, however, evaluated and compared the students test scores and performance over the semester while providing both online and in-class learning.…”
Section: Discussionmentioning
confidence: 99%
“…A study published in 2012 determined that the majority of predoctoral students in the United States of America (USA), United Kingdom (UK) and Australia were instructed on 3D anatomical structures from CBCT imaging as part of their curriculum. CBCT imaging interpretation training was provided in about half of the Dental Schools in the USA and Australia, and in one-third in the UK schools 7 . Adibi et al 1 stated that CBCT learning as a whole had to be promoted in the predoctoral curriculum.…”
Section: Introductionmentioning
confidence: 99%
“…Although the results obtained by the undergraduate student and the orthodontist were similar, we emphasized that the exploration of CBCT in dental schools might improve the utilization of this technology in clinical practice. CBCT has been shown to be an excellent modality for maxillofacial imaging, and numerous applications in the oral and maxillofacial region have been reported 22,23 . The use of 3D CBCT images in oral radiology courses further familiarizes students with 3D anatomy and prepares them to interpret 3D images.…”
Section: Discussionmentioning
confidence: 99%
“…With insufficient data or information available at this stage, it is difficult to compare the adoption of CBCT machines in Australia with that overseas. It was reported that in 2012 there were 39 CBCT clinics registered in Norway and Parashar et al . reported the active use of CBCT in 50 US dental schools, 10 UK dental schools and one Australian dental school, with more schools preparing to acquire the technology.…”
Section: Discussionmentioning
confidence: 99%